What has been the impact financial and fiscal, on pension scheme in Colombia offered during the years 2007 to 2013? (2013)
This essay is the result of a research documentary on pension regimes and the financial and fiscal impact that has been presented in our country Colombia from years 2007 the 2013, for this we will review background documents and pension reforms.